COVID-19's impact on Fintech adoption: Behavioral intention to use the financial portal - Arfan Shahzad; Nurhana Zahrullail; Ahsan Akbar; Hana Mohelska; Arsalan Hussain (Journal of Risk and Financial Management, 2022)
As Fintech has grown exponentially in recent years, several researchers have examined how information technology is applied in the financial services sector, with a focus on the extended practice of its application. However, fewer studies have investigated the factors influencing the acceptance of Fintech services. In order to examine how consumers adopt Fintech services, this research presents an enhanced technology acceptance model (TAM) that integrates perceived usefulness, perceived ease of use, user innovativeness, and trust as factors of attitude towards using Fintech platforms and behavioral intention to use Fintech platforms. The questionnaires were sent to 867 of Portal MyAzZahra's customers, and 273 complete questionnaires were received. The data were then analyzed to comprehend whether the proposed hypotheses were accepted or rejected. The findings depict that consumers' trust, perceived ease of use, and customer innovation in Fintech services substantially impact the attitude towards adoption and behavioral intention to use the Fintech online platform. However, perceived usefulness does not significantly influence the attitude towards adoption and the behavioral intention to use the online loan aggregator. By integrating these factors into Fintech services with TAM, this study adds to the literature on adopting Fintech services by offering a more holistic perspective of the factors affecting consumers' attitudes
Keywords: 650; technology acceptance model (TAM); Fintech services; attitude; trust and perceived ease of use